Positive Impacts of Aphanizomenon Flos Aquae Extract on Obesity-Related Dysmetabolism in Mice with Diet-Induced Obesity - Simona Terzo; Pasquale Calvi; Marta Giardina; Giacoma Gallizzi; Marta Di Carlo; Domenico Nuzzo; Pasquale Picone; Roberto Puleio; Flavia Mulè; Stefano Scoglio; Antonella Amato (Cells, 2023)
The present study evaluated the ability of KlamExtra®, an Aphanizomenon flos aquae (AFA) extract, to counteract metabolic dysfunctions due to a high fat diet (HFD) or to accelerate their reversion induced by switching an HFD to a normocaloric diet in mice with diet-induced obesity. A group of HFD mice was fed with an HFD supplemented with AFA (HFD-AFA) and another one was fed with regular chow (standard diet—STD) alone or supplemented with AFA (STD-AFA). AFA was able to significantly reduce body weight, hypertriglyceridemia, liver fat accumulation and adipocyte size in HFD mice. AFA also reduced hyperglycaemia, insulinaemia, HOMA-IR and ameliorated the glucose tolerance and the insulin response of obese mice. Furthermore, in obese mice AFA normalised the gene and the protein expression of factors involved in lipid metabolism (FAS, PPAR-γ, SREBP-1c and FAT-P mRNA), inflammation (TNF-α and IL-6 mRNA, NFkB and IL-10 proteins) and oxidative stress (ROS levels and SOD activity). Interestingly, AFA accelerated the STD-induced reversion of glucose dysmetabolism, hepatic and VAT inflammation and oxidative stress. In conclusion, AFA supplementation prevents HFD-induced dysmetabolism and accelerates the STD-dependent recovery of glucose dysmetabolism by positively modulating oxidative stress, inflammation and the expression of the genes linked to lipid metabolism.